A Friend in Need or a Business Indeed? Disabled Bodies and Fraternalism in Victorian Ontario - Galer, Dustin (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2010)
Abstract During the period of early capitalism in Ontario, disabled workers were forced to find ways to survive following an injury. Affordable insurance offered by fraternal societies provided limited protection for many working-class families but was not a reliable source of financial support for injured and disabled workers. Even when insurance disability benefits were a factor, many injured workers soon found themselves in a position of financial hardship. Fraternal insurance reflected many of the same barriers facing disabled workers and as a result, represents a microcosm of wider social and institutional treatment of individuals with disabilities during this period.